Long-finned pilot whale (Globicephala melas, Traill 1809) subspecies in the Atlantic Ocean: Are there differences in their skulls? - Marina, Tomas Ignacio; Marchesi, María Constanza; Prosser Goodall, Rae Natalie (Marine Mammal Science)
Long-finned pilot whales (Globicephala melas) are among the few odontocetes that show an anti-tropical distribution. The North Atlantic subspecies (G. m. melas, Traill 1809) has been widely studied in the east and west coast, but there is little previous information on the Southern subspecies (G. m. edwardii, A. Smith 1834). Here we investigated the skull morphometry of both populations, subspecies status nowadays, with the aim of characterizing and comparing them. We examined a total of 93 adult skulls. In all skulls, 21 measurements were analyzed. Our results clearly differentiated skull morphology between long-finned pilot whale subspecies, being the following characters the most important in the discrimination: width of rostrum at base, and at ¼, ½ and ¾ length, length of rostrum to internal and external nares, and length and height of temporal fossa. Overall, G. m. edwardii specimens showed a longer skull, larger rostrum, wider nares, larger temporal fossa and longer orbits than G. m. melas. We suggest that these strong dissimilarities might have functional implications for feeding habits, diving behaviour and sound production capabilities. This is the first study that proves that skull morphometry in long-finned pilot whale subspecies presents significant differences. Fil: Marina, Tomas Ignacio. Museo Acatushún de Aves y Mamíferos Marinos Australes; Argentina. Universidad Nacional de General Sarmiento; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Marchesi, María Constanza. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Prosser Goodall, Rae Natalie. Museo Acatushún de Aves y Mamíferos Marinos Australes; Argentina